Church building and society in the later Middle Ages - Byng, Gabriel (Cambridge studies in medieval life and thought. Fourth series, 2017)
The construction of a church was undoubtedly one of the most demanding events to take place in the life of a medieval parish. It required a huge outlay of time, money and labour, and often a new organisational structure to oversee design and management. Who took control and who provided the financing was deeply shaped by local patterns in wealth, authority and institutional development - from small villages with little formal government to settlements with highly unequal populations. This all took place during a period of great economic and social change as communities managed the impact of the Black Death, the end of serfdom and the slump of the mid-fifteenth century. This original and authoritative study provides an account of how economic change, local politics and architecture combined in late-medieval England. It will be of interest to researchers of medieval, socio-economic and art history.